2019
DOI: 10.3390/joitmc5040088
|View full text |Cite
|
Sign up to set email alerts
|

Firm Constraints on the Link between Proactive Innovation, Open Innovation and Firm Performance

Abstract: This study aims to examine the impacts of firm constraints and proactive innovation on firm performance, using a sample of 3504 small and medium enterprises (SMEs) in Vietnam from 2011–2015. Our findings suggest that technological innovations in general are beneficial to firm performance, increasing firm sales and profits. Further filtering innovations into two categories of proactive and reactive ones, we find that reactive innovation negatively affects firm performance, consistent with the view that proactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 66 publications
1
16
0
Order By: Relevance
“…The latter represents the reaction of organisations after the effects of Organisational resilience trends influence elements of a BM (ex-post), while the former allows the recognition and prevention of trends before they occur (ex-ante). Several studies reported that a proactive strategy regarding business management is associated with higher organisational performance (Barber and Warn, 2005;Hacklin et al, 2018;Liem et al, 2019). Barber and Warn (2005) found that proactive leadership is linked to more successful project management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter represents the reaction of organisations after the effects of Organisational resilience trends influence elements of a BM (ex-post), while the former allows the recognition and prevention of trends before they occur (ex-ante). Several studies reported that a proactive strategy regarding business management is associated with higher organisational performance (Barber and Warn, 2005;Hacklin et al, 2018;Liem et al, 2019). Barber and Warn (2005) found that proactive leadership is linked to more successful project management.…”
Section: Discussionmentioning
confidence: 99%
“…Barber and Warn (2005) found that proactive leadership is linked to more successful project management. Equally, firm performance is negatively influenced by reactive innovations (Liem et al, 2019). However, Sekkal et al (2020) reported that reactive and proactive decisionmaking impact the business world, concluding that proactive decision-making is important in anticipating situations before they occur, while reactive decision-making is important for real-time situations.…”
Section: Discussionmentioning
confidence: 99%
“…Reference Inbound Open Innovation [13], [26] [27], [28], [33], [34], [37], [38], [39], [40], [41], [42], [44]. [46], [47], [48], [49], [50],…”
Section: Table IX Open Innovation Manifest Open Innovation Manifestmentioning
confidence: 99%
“…These challenges are affecting the way that organizations are managed. According to Liem et al [1] there are various limitations SMEs might face that make their ability to innovate very difficult such as absence of advantaged information from experts, human resources, and technology particularly in developing countries. In fact, the universal nature of the new marketplace needs active players to globalize their operations [2].…”
Section: Introductionmentioning
confidence: 99%